Development of 3D porous graphene/manganese dioxide/polyaniline hybrid film for flexible all-solid-state asymmetric supercapacitor - Ghosh, Kalyan (2018)
There is increasing demand for safe, environmentally benign energy storage devices in portable electronic appliances, wearable gadgets, flexible displays, and other personal multimedia devices. The flexible solid-state supercapacitor can be used as an energy storage device to meet these future needs. Carbonaceous electrode materials such as activated carbon, carbon nanotubes, and graphene are recognized as promising electrode materials for flexible solid-state supercapacitor due to their high power density and long cyclic stability. However, their energy storage is limited to the electrochemical double-layer mechanism that cannot provide the required high energy density. This is in contrast to other materials such as metal oxides and conducting polymers that can support high energy densities through the pseudocapacitive energy storage mechanism. However, most metal oxides are costly and toxic, while conducting polymers suffer from poor long-term cyclic stability. Thus, for this work, MnO2 is selected due to its inexpensive and non-toxic in nature. Furthermore, it is essential to synthesize and develop hybrid electrode materials in which the disadvantages of each constituent component material can be mitigated. This work focuses on the synthesis and development of novel 3D ternary composite materials based on reduced graphene oxide (RGO), MnO2, and polyaniline (PANI). Our studies revealed that the morphology and microstructure of the 3D ternary composite system can be optimized to develop high performance flexible solid-state asymmetric supercapacitors. At first, a novel 3D hollow urchin-shaped coaxial manganese dioxide@polyaniline (MnO2@PANI) composite and a 3D graphene foam (GF) were synthesized for use as positive and negative electrodes, respectively to fabricate an all-solid-state flexible asymmetric supercapacitor (ASC). Polyvinyl alcohol/potassium hydroxide (PVA/KOH) gel was used as the electrolyte. The selection of KOH based electrolyte over acidic electrolyte was to prevent the Ni foam current collector from the corrosive effect of acidic electrolyte. Moreover, PVA/KOH electrolyte shows high ionic mobility. The coaxial MnO2@PANI composite was synthesized by employing a hydrothermal route followed by oxidation aniline without the use of an external oxidant The solid-state asymmetric supercapacitor (MnO2@PANI//GF) had a high energy density of 37 Wh kg−1 at a power density of 0.386 kW kg−1 and a good cyclic stability with ~11% capacitance loss was observed after 5000 cycles. A hybrid film comprising of novel ternary composite 3D porous RGO/MnO2@PANI hybrid material was successfully developed as the positive electrode material for the ASC device. The flexible composite film was synthesized by vacuum filtration of the graphene oxide (GO) and MnO2@PANI dispersion, followed by chemical reduction of the residue film in a hydrothermal autoclave. To increase the energy density of the negative electrode material 3D graphene aerogel with high surface area was synthesized using a nonionic triblock copolymer Pluronic F-68 solution as a soft-template following the hydrothermal route. The pluronic copolymer had dual roles, firstly it enabled effective dispersion of GO in water, and secondly, it assisted the formation of a stable 3D pillared hydrogel assembly. The solid-state ASC (graphene aerogel//RGO/MnO2@PANI) had a very high energy density of 38.12 Wh kg−1 at a power density of 1.191 kW kg−1 and 85.8% capacitance retention after 5000 cycles. Finally, the approach to significantly increase energy density of the supercapacitor by enlarging operating voltage window through the use of two metal oxides that have a large difference in work function was investigated. Through the use of MnO2 and MoO3 in the positive and negative electrodes respectively, and adopting a 3D heterogeneous composite based on PANI and RGO, the operating voltage window was successfully widened to 0−1.6 V. A ternary composite of sandwich-type PANI decorated 3D porous MnO2−RGO hybrid film (PANI/(MnO2−RGO)/PANI) was synthesized as the positive electrode, while a 3D molybdenum oxide/graphene aerogel (MoO3/GF) composite material was developed to use as the negative electrode material. The asymmetric supercapacitor (MoO3/GF//PANI/(MnO2−RGO)/PANI) exhibited a dramatically high energy density of 51.91 Wh kg−1 at a power density of 0.838 kW kg−1. The asymmetric cells were flexible, and three cells connected in series could illuminate a green LED for 62 s. This showed that the novel 3D ternary composite materials developed in the current work can be employed to fabricate a flexible ASC that is reliable and has very high energy density.